Research methods and data analysis in the social sciences - Herzog, Thomas R. 1942- (HarperCollins Colege Publishers, 1996)
Employing a clear, straightforward framework, this text focuses on the types of data most commonly produced by the basic research methods of observation, survey, and experiment, the text pairs each method chapter with a chapter on the analysis of the types of results usually obtained with that type of research.